2020
DOI: 10.1159/000509203
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Obesity in Acne Keloidalis Nuchae Patients: A Hypothesis from a Brazilian Study

Abstract: • Acne keloidalis nuchae (AKN) is a chronic inflammatory condition that almost exclusively affects the occipital and nape areas, being much more common in men, especially in African descendants from puberty to 50 years of age. • AKN has long been associated with friction and local trauma due to shirt collars, hats, helmets, and close shaves as triggering factors. Furthermore, keratinization disorders of genetic origin, folliculitis decalvans, seborrhea, increased androgen levels, the use of some medications, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…An increase in angiotensin II concurrently leads to increased expression of TGF-1, which promotes fbrogenesis [22]. Regarding obesity, increased body mass index (BMI) often results in increased skin folds on the neck and occipital scalp, which can induce mechanical trauma to the area, potentially causing AKN [22,24]. AKN has also been reported in patients with acanthosis nigricans, a cutaneous marker of obesity and metabolic syndrome [25].…”
Section: Resultsmentioning
confidence: 99%
“…An increase in angiotensin II concurrently leads to increased expression of TGF-1, which promotes fbrogenesis [22]. Regarding obesity, increased body mass index (BMI) often results in increased skin folds on the neck and occipital scalp, which can induce mechanical trauma to the area, potentially causing AKN [22,24]. AKN has also been reported in patients with acanthosis nigricans, a cutaneous marker of obesity and metabolic syndrome [25].…”
Section: Resultsmentioning
confidence: 99%
“…Obesity poses a risk factor for numerous clinical conditions, including dermatological disorders such as hidradenitis suppurativa (HS), and psoriasis 17 . According to previous studies, obesity is a risk factor for developing AKN, and the risk of developing AKN is also increased in obese patients 18 . Both obesity and diabetes mellitus are associated with gout 19 .…”
Section: Discussionmentioning
confidence: 99%
“…17 According to previous studies, obesity is a risk factor for developing AKN, and the risk of developing AKN is also increased in obese patients. 18 Both obesity and diabetes mellitus are associated with gout. 19 Using a large population-based study, we have previously shown that AKN is associated with hidradenitis suppurativa (HS), another chronic inflammatory disorder that pathologically targets the hair follicle.…”
Section: Ta B L E 1 Descriptive Characteristics Of the Study Populationmentioning
confidence: 99%
“…It is unknown why the predilection site for this condition is the occipital region. Several explanations for this phenomenon have been suggested, but not proven, including elevated levels of androgens in the scalp, increase in mast cells and dermal papillary dilatation in the nuchal area [ 2 ] as well as friction of the scalp skin folds and obesity [ 4 ]. Most studies describe a history of chronic friction in the area with short haircuts, frequent wearing of tight collars, hats and helmets in certain professions (e.g.…”
Section: Introductionmentioning
confidence: 99%